Labioplasty barsky technique in patients with complete bilateral cleft lip: Labioplasti secara teknik Barsky pada pasien celah-bibir bilateral - Raside, Hadira (Makassar Dental Journal PDGI Makassar, 2024)
Bilateral cleft lip is occured on both sides of the premaxilla either complete or incomplete so that in this situation there is no nor-mal side for comparison. Cleft lip and palate deformities are generally congenital abnormalities that require comprehensive ma-nagement. Barsky's technique is rarely used, but it is important to know the results in cases of BCC komplit. In this case review, a 16-month-old boy with a diagnosis of bilateral complete labiognatopalatoschizis underwent labioplasty with the Barsky tech-nique on his CL. Labioplasty was performed under general anaesthesia at the Unhas Teaching Dental Hospital. The Barsky tech-nique is a development of the Veau II technique, indicated in cases of CL with protrusive premaxilla and short prolabiun. It was concluded that CL can be treated with Barsky technique labioplasty.